A case of dual ectopic thyroid - Hussain, S. Zahir; Ayub, Muhamed Faizal (International Surgery Journal, 2017)
The presence of two ectopic foci of thyroid tissue in a single patient is an uncommon presentation. Ectopic thyroid reportedly has a low incidence. We are reporting here a case of dual ectopic thyroid present in the lingual and sub hyoid region in a 33 years old lady with short stature and hypothyroidism. Ultrasonography of the neck had revealed no thyroid gland in its normal anatomical position. The presence of ectopic thyroid tissue in the lingual and sub hyoid region were confirmed with a technetium-99m sodium per technetate thyroid scan.